Synergistic effect of glycyrrhizic acid and cellulose nanocrystals for oil-water interfacial stabilization. (November 2021) - Ma, Lulu; Bertsch, Pascal; Wan, Zhili; Yang, Xiaoquan; Fischer, Peter
Abstract: In this work, the interfacial and bulk properties of oil-in-water emulsions stabilized by glycyrrhizic acid (GA), structurally a saponin and cellulose nanocrystals (CNC) as a co-stabilizer are investigated at different ionic strengths. The influence of GA, CNC, and NaCl concentration on the bulk stabilization of the emulsion as well as on the adsorption behavior and dilatational viscoelasticity at a model oil-water interface are discussed. At the oil-water interface GA adsorbs with appropriate CNC concentration due to salt-induced charge screening, but desorbs from the interface into bulk by excessive increase of the CNC concentration. An interfacial synergistic effect between GA and CNC was found at GA concentrations below interfacial saturation, attributed to the formation of interfacial GA-CNC complexes. In emulsions, the synergistic stabilization concentrations of the compounds are found at higher concentration of 1 wt% GA, 1 wt% CNC, and 20 mM NaCl. FTIR measurements suggest complexation of GA and CNC via hydrogen bonds and intermolecular interactions. The results provide evidence of network formation due to GA-CNC complexes at the interface and aggregation in the continuous phase, which eventually stabilize the emulsion systems. Highlights: Glycyrrhizic acid, a saponin and cellulose nanocrystal exhibited antagonistic effects at oil-water interfaces. These antagonistic effects were found to convert to synergistic effects by salt induced charge screening. The synergistic effects between GA and CNC were proven to exist both at the interface and in bulk via hydrogen bonds.